Modeling Mixed Layer Flow Under Leads in Sea Ice - Smith IV, David C (1999)
OBJECTIVES. The objectives of this study are to examine convectively driven mixed layer circulations under leads in Arctic Ocean sea ice. A specific goal is to determine under what circumstances eddy formation is favored and do the eddies which are generated in leads have chracteristics of those seen in observations of Arctic mixed layer eddies. APPROACH. During the previous several years of support, a nonhydrostatic high resolution convection model has been developed for the study of ocean flow beneath leads in sea ice. The results obtained thus far have been for two dimensional flow fields. Recently however, the model has been adapted to three dimensions. The three dimensional model is used in initial value and boundary forced numerical experiments in which a wide range of realistic lead conditions are simulated. These experiments are conducted where possible to coincide with comparable laboratory experimentation (also conductedhere at ASU) on convection from line segment sources in rotating frames.